2023
DOI: 10.4244/eij-d-22-00627
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial appendage occlusion

Abstract: Prevention of stroke represents a goal of primary importance in health systems due to its associated morbidity and mortality. As several patient groups with increased stroke rates have been identified, multiple approaches have been developed and implemented: oral anticoagulation (OAC) for patients with atrial fibrillation, surgical and percutaneous revascularisation in patients with carotid disease, device closure for patients with patent foramen ovale, and now, left atrial appendage occlusion (LAAO) for selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
0
11

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(130 citation statements)
references
References 109 publications
(162 reference statements)
0
110
0
11
Order By: Relevance
“…were independently able to show, that size selection and implantation supported by computational assisted sizing and modelling can potentially lead to a reduction in the commonly observed peri‐device leaks, seen in up to 40% of cases at post‐procedural LAA closure imaging 29–31 . The incidence of PDL varies between the general device‐design (“plug” vs. “pacifier”) 20 . Up to this time, the consensus remains that a PDL > 5 mm is defined as incomplete LAAO and requires either continuation of anticoagulation or interventional leak closure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…were independently able to show, that size selection and implantation supported by computational assisted sizing and modelling can potentially lead to a reduction in the commonly observed peri‐device leaks, seen in up to 40% of cases at post‐procedural LAA closure imaging 29–31 . The incidence of PDL varies between the general device‐design (“plug” vs. “pacifier”) 20 . Up to this time, the consensus remains that a PDL > 5 mm is defined as incomplete LAAO and requires either continuation of anticoagulation or interventional leak closure.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] The incidence of PDL varies between the general devicedesign ("plug" vs. "pacifier"). 20 Up to this time, the consensus remains that a PDL > 5 mm is defined as incomplete LAAO and requires either continuation of anticoagulation or interventional leak closure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Limited data on the clinical implications of PDL have led to conflicting findings. So far, the consensus has been that PDL larger than 5 mm indicates incomplete LAAO and necessitates either ongoing anticoagulation or intervention for leak closure 54 (Figure 9).…”
Section: Peridevice Leaks (Pdl)mentioning
confidence: 99%
“…For patients eligible for OAC therapy, studies have demonstrated that LAAC is non-inferior to warfarin in preventing stroke and SE. [50] The results of the left atrial appendage closure vs. novel anticoagulation agents in AF (PRAGUE-17) study indicate that LAAC is not inferior to NOACs in preventing stroke, SE, major bleeding, or clinically relevant non-major bleeding events, as well as surgery-related complications. [51] Additionally, it significantly reduces clinically relevant non-major bleeding events unrelated to the procedure.…”
Section: Stroke Preventionmentioning
confidence: 99%